2022
DOI: 10.1080/19420862.2022.2122957
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and biological impact of metal-catalyzed oxidation of IgG1 monoclonal antibodies and antibody-drug conjugates via reactive oxygen species

Abstract: Biotherapeutics are exposed to common transition metal ions such as Cu(II) and Fe(II) during manufacturing processes and storage. IgG1 biotherapeutics are vulnerable to reactive oxygen species (ROS) generated via the metal-catalyzed oxidation reactions. Exposure to these metal ions can lead to potential changes to structure and function, ultimately influencing efficacy, potency, and potential immunogenicity of the molecules. Here, we stress four biotherapeutics of the IgG1 subclass (trastuzumab, trastuzumab em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 85 publications
(96 reference statements)
4
17
0
Order By: Relevance
“…We note that Glover et al recently showed a less pronounced effect of Fe­(II) compared to Cu­(II) during metal-catalyzed oxidation of several mAbs and mAb-derived conjugates . They did not identify specific binding sites for Fe­(II), but this observation does not exclude the binding of Fe­(III).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We note that Glover et al recently showed a less pronounced effect of Fe­(II) compared to Cu­(II) during metal-catalyzed oxidation of several mAbs and mAb-derived conjugates . They did not identify specific binding sites for Fe­(II), but this observation does not exclude the binding of Fe­(III).…”
Section: Discussionmentioning
confidence: 62%
“…29,48 Figure 11B shows the crystal structure of a mononuclear citrate/Fe(III) complex determined by Matzapetakis et al 29 We note that Glover et al recently showed a less pronounced effect of Fe(II) compared to Cu(II) during metal-catalyzed oxidation of several mAbs and mAb-derived conjugates. 49 They did not identify specific binding sites for Fe(II), but this observation does not exclude the binding of Fe(III). The experimental test of Glover et al relied on the site-specific formation of reactive oxygen species, especially hydroxyl radicals, via the Fenton reaction of Fe(II) with hydrogen peroxide.…”
Section: ■ Discussionmentioning
confidence: 97%
“…In addition, polymerization conditions must be carefully optimized to be compatible with proteins, which require the use of aqueous solvents and low temperatures; as a result, achieving a balance between mild polymerization conditions and low polymer dispersity is often challenging. Finally, ATRP uses transition metal catalysts such as copper, which is a potential concern as metal ions can bind to proteins and trigger chemical degradation, including oxidation and fragmentation [ 264 , 265 ].…”
Section: Protein/peptide Therapeutics That Are Enhanced Through Chemi...mentioning
confidence: 99%
“… 16 As the level of MetO increases, the resulting SPR data can provide a readout in terms of reduced binding affinity. 16 , 17 Recently, a rapid SPR assay was developed to quickly detect Met oxidation in both the antigen-binding fragment (Fab) and Fc domains. 18 Using a model therapeutic IgG1κ mAb, NISTmAb, 19 , 20 specific molecular probes were used to assess the binding to one region in the Fc (Protein A) and two regions in the Fab (Protein L, F peptide).…”
Section: Introductionmentioning
confidence: 99%